Analysis of the determinants of early discontinuation of exclusive breastfeeding - Faleiro, Daiane Cella; Scherer, Milena Raquel; Martins, Wesley; Strada, Cinthya de Fátima Oliveira (JRG Journal of Academic Studies, 2023)
Objective: to identify the factors that led to the early interruption of exclusive breastfeeding in children under six months of age in a Family Health Strategy unit. Methodology: this is a descriptive and exploratory qualitative research, consisting of 13 participants who underwent early interruption of exclusive breastfeeding in a Family Health Strategy in the city of Itaipulândia - Paraná. To collect data, a questionnaire was applied containing information about the sociodemographic profile and information focused on the central theme of the research. The collected data was tabulated and statistical analysis was carried out based on the results obtained. Results: the participants were aged between 30 and 59 years old, employed with a formal contract, in a stable union, white race/color, with completed higher education and Catholic religion. Return to work, weak milk, breast problems, introduction of artificial nipples and family influences were the main reports presented by participants for the early interruption of exclusive breastfeeding before the baby's six months of life. Conclusion: returning to work stood out as the main factor in the early interruption of exclusive breastfeeding, since occupational demands often limit the availability and continuity of exclusive breastfeeding.